Representation of Feminism in The Film Lucy Through Roland Barthes’ Semiotic Analysis - Marpaung, Claudia Yossi Grace; Heriyanto, Eko; Ayunda, Nenin Astiti (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
This study examines the representation of feminism in the film Lucy (2014) through Roland Barthes' semiotic analysis. This research employs a qualitative descriptive approach using Roland Barthes' semiotic analysis, which explores denotation, connotation, and myth. By analyzing the signs and symbols present in the film, the research aims to uncover the underlying meanings and messages regarding feminism. The data in this research will be collected using documentation techniques and literature studies. The results of this research show that there are multiple signs of feminism that are shown through this film, such as women's autonomy being undermined and their consent not being respected, women are often viewed solely as objects of desire and subjected to physical aggression. However, Lucy showed that women had the capacity to assert themselves and change their circumstances, women had the capability to confront challenges and overcome obstacles, and women could take bold steps and contribute actively to their outcomes.